(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The field of chronotherapeutics is concerned with administering medication in accordance with the inherent activities of a disease over a predetermined amount of time. This approach is based on the observation that risk factors, pharmacologic sensitivity, and the pharmacokinetics of many drugs are all correlated with the peak-to-trough rhythmic activity in disease symptoms. Since the circadian clock controls 24 hour cycles of biochemical, physiological, pathological, and behavioral processes, the efficacy and toxicity of many medications varies depending on the time of administration. If an illness exhibits diurnal fluctuation in its symptoms, then medication release need ideally fluctuate over time to correspond with the disease’s circadian rhythms. Since consistent drug plasma concentrations cannot result in the best possible therapeutic outcome, the precise moment that patients take their medications is crucial and has a big influence on treatment effectiveness. The medicine must be administered at the proper site of action, at the right time, and in the right dosage for the therapy to be effective. This will minimize adverse effects, maximize therapeutic impact, and improve patient compliance. Therefore, in the era of contemporary medicines, time-programmed release delivery systems may show to be more advantageous for the patient than traditional methods. Release modified systems may expedite the drug discovery process much more than hunting for novel medications.